Using egg density and egg mass techniques for incubation stage assessment to predict hatch dates of Greater Flamingo Phoenicopterus ruber roseus eggs. - Jarrett, N; Mason, V; Wright, L; Levassor, V (Wildfowl, 2013)
x.